INVESTIGATING THE COGNITIVE PROCESSES IN POST-EDITING ACTIVITY USING THINKING ALOUD PROTOCOLS - Gharizi Matiini (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
The study aims to investigate the cognitive processes and meta-cognitive strategies used by the post-editor when doing the post-editing activity. It examines the way the post editor reads, thinks, speculates, and makes decision to the machine translation results and correcting the problems founds from the translated text. Thinking Aloud Protocols (TAPs) is used as the approach of the study to record the meta-cognitive strategies applied by the post editor. Several instruments such as video recording tools, machine-translated text, and timer are operated during the data collection. From the study, it is shown that reasoning and problem solving become the most running strategy from the post-editor. It occurs since the post-editor mostly looks for the problems and tries to find a way of correcting mistakes from the translation. The result also shows that the post-editor tries to comprehend the problems and decides the accurate decision when song the post-editing. The cognitive process and meta-cognitive strategies are quite different between the translator and the post-editor.